Straight to the top : CIO leadership in a mobile, social, and cloud-based world - Smith, Gregory S., 1963- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Essential reading for IT professionals with aspirations toward the top IT spot, and forsitting CIOs looking to refine their mobile, social and cloud strategies and knowledge The definitive work on how to achieve leadership success in IT, Straight to the Top, SecondEdition reveals how the role of the CIO is changing due to major trends associated withconsumer and enterprise products and technologies driving new mobile solutions in today'sorganizations; cloud computing and the move away from controlled / internally managed datacenters to pay as you use and elastic cloud infrastruc.
Preface -- Acknowledgments -- Key change drivers and trends impacting the CIO role today -- Why the role of the CIO continues to change -- Technologies and trends driving today's IT innovation -- IT standards and governance and the impact of consumer devices -- Service level agreements : a key to improved customer expectations and better contracts -- About the author -- Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Chief information officers -- Vocational guidance; Information technology -- Management -- Vocational guidance; Information resources management -- Vocational guidance; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Business; Electronic books; Electronic books